Transfer of Land Ownership through a Binding Agreement of Sale and Purchase under the Hand (Comparative Study Reviewed in the Perspective of Civil Law and Islamic Law) - Robby Awaluddin Jamil; Emilda Kuspraningrum; Amsari Damanik (Publikasi Indonesia, 2024)
This study aims to analyze the legal strength of the binding sale and purchase agreement under the hand and analyze the legal protection for the buyer if the seller commits a Default on the binding sale and purchase agreement. This research is a doctrinal research. In practice, in the implementation of the Sale and Purchase Agreement, there are still many development actors who do not make the Sale and Purchase Agreement in front of a notary in the form of an authentic deed, but make it in the form of a deed under hand. A Sale and Purchase Agreement made with an authentic deed and a deed under hand has a fundamental difference in terms of its evidentiary strength. The Sale and Purchase Binding Agreement in its implementation in the community cannot always run smoothly, sometimes some factors limit the engagement in continuing or until it becomes invalid, The case can be known that PPJB can be asked for compensation if it is not by the agreement of the parties in the agreement, which in this case the seller commits a breach of performance, while the buyer, in this case, is in good faith by fulfilling what has been As stated in the PPJB, the Agreement can be cancelled if it is not by the subjective conditions or the objective requirements of the agreement as stipulated in article 1320 of the Civil Code.